Pedagogical resistance alternatives to neoliberal educational discrimination exercised by white-masculine-rich power - Molina, Nelson (Revista Innova Educación, 2020)
With the purpose of contributing to support the idea that neoliberal educational policies are discriminatory and use the educational system to exercise discrimination of race, gender and class in favor of the masculine-white-rich power, the following reflection article compiled, from the main databases and repositories, some works written in English that orbit around this subject. The purpose was to make known in Spanish speaking something of what has been discussed in English about racism in education. The review also revealed the existence of resistance educational spaces: in essence, a pedagogical perspective based on the intimacy of dialogue in classrooms, conversation, argumentation and narrative.